Genome-wide DNA methylation analysis reveals different methylation patterns in Chinese indigenous sheep with different type of tail - Caiye, Zhu; Song, Shuzhen; Li, Minna; Huang, Xaioyu; Luo, Yan; Fang, Suli (Frontiers in Veterinary Science, 2023)
Background: The study was aimed to analyze the difference of genome-wide DNA differential methylation in Lanzhou Large-tailed sheep, Altay sheep and Tibetan sheep, which the typical breeds with different type tails, as to screen the differentially methylated genes (DMGs) that affect the type of tails. Methods: whole genome bisulfite sequencing (WGBS). The degree of genome-wide DNA methylation, differentially methylated regions (DMRs) and DMGs were analyzed. The candidate genes affecting the tail type of sheep were identified by GO and KEGG pathway enrichment analysis of DMGs. Results: we identified 68603 different methylated regions (DMCs) and 75 differentially methylated genes (DMGs) associated with these DMCs. Functional analysis showed that these DMGs were mainly enriched in biological process, cellular component and molecular function, Some of the genes in these pathways are involved in fat metabolism: NFATC4, LPIN2, MGAT2 and MAT2B. Conclusions: Our results may help to further understand the epigenetic regulation mechanisms of deposition of fat in the tail of sheep.